ANALYSIS OF SLANG WORD IN HARRY POTTER AND THE CHAMBER OF SECRETS MOVIE - Ginting, Novfiana Br; Prayuda, Meikardo Samuel; Ginting, Fiber Yun Almanda; Siahaan, Junita; Lumbanraja, Bogor (Jurnal Ilmiah Aquinas, 2025)
This research analyzed the kinds of slangword used in harry potter and the chamber of secrets movie. The objectives of this research were to find out the kinds of slang word in harry potter and the chamber of secrets movie, found the most dominant kind of slang word used and the meaning of the most dominant slang word that used. This research applied descriptive qualitative research. The source of data was Harry Potter and the chamber of secrets movie. There were one season film had been analyzed. Based on the analysis, there were three kinds of slang word used in harry potter and the chamber of secrets movie, there were fresh and creative slang word, compounding slang word, and imitative slang word. It consisted of 32 slang word of fresh and creative (82,7%), 51 slang word of compounding (59%), and 3 imitative of slang word (4%). The slang word “muggle” most dominant slang word used in this movie.